Home-based Reach-to-Grasp training for people after stroke is feasible: a pilot randomised controlled trial. (July 2017) - Turton, AJ; Cunningham, P; van Wijck, F; Smartt, HJM; Rogers, CA; Sackley, CM; Jowett, S; Wolf, SL; Wheatley, K; van Vliet, P
Objective: To determine feasibility of a randomised controlled trial (RCT) of home-based Reach-to-Grasp training after stroke. Design: single-blind parallel group RCT. Participants: Residual arm deficit less than 12 months post-stroke. Interventions: Reach-to-Grasp training in 14 one-hour therapist's visits over 6 weeks, plus one hour self-practice per day (total 56 hours). Control: Usual care. Main Measures: Action Research Arm Test (ARAT), Wolf Motor Function Test (WMFT), pre-randomisation, 7, 12, 24 weeks post-randomisation. Results: Forty-seven participants (Reach-to-Grasp=24, usual care=23) were randomised over 17 months. Reach-to-Grasp participants received a median (IQR) 14 (13, 14) visits, and performed 157 (96, 211) repetitions per visit; plus 30 minutes (22, 45) self-practice per day. Usual care participants received 10.5 (5, 14) therapist visits, comprising 38.6 (30, 45) minutes of arm therapy with 16 (6, 24) repetitions of functional tasks per visit. Median ARAT scores in the reach-to-grasp group were 8.5 (3.0, 24.0) at baseline and 14.5 (3.5, 26.0) at 24 weeks compared to median of 4 at both time points (IQR: baseline (3.0, 14.0), 24 weeks (3.0, 30.0)) in the usual-care group. Median WMFT tasks completed at baseline and 24 weeks were 6 (3.0, 11.5) and 8.5 (4.5, 13.5) respectively in the reach-to-grasp group and 4 (3.0, 10.0), 6 (3.0, 14.0) in the usual care group. Incidence of arm pain was similar between groups. The study was stopped before 11 patients reached the 24 weeks assessment. Conclusions: An RCT of home-based Reach-to-Grasp training after stroke is feasible and safe. With ARAT being our preferred measure it is estimated that 240 participants will be needed for a future two armed trial.